Evaluating mental health service use during and after emergency department visits in a multisite cohort of Canadian children and youth. Issue 1 (4th December 2017) - Cappelli, Mario; Cloutier, Paula; Newton, Amanda S.; Fitzpatrick, Eleanor; Ali, Samina; Dong, Kathryn A.; Gray, Clare; Kennedy, Allison; Lyons, John S.; Polihronis, Christine; Rosychuk, Rhonda J.
Abstract: Objectives: The goal of this study was to examine the mental health needs of children and youth who present to the emergency department (ED) for mental health care and to describe the type of, and satisfaction with, follow-up mental health services accessed. Methods: A 6-month to 1.5-year prospective cohort study was conducted in three Canadian pediatric EDs and one general ED, with a 1-month follow-up post-ED discharge. Measures included 1) clinician rating of mental health needs, 2) patient and caregiver self-reports of follow-up services, and 3) interviews regarding follow-up satisfaction. Data analysis included descriptive statistics and the Fisher's exact test to compare sites. Results: The cohort consisted of 373 children and youth (61.1% female; mean age 15.1 years, 1.5 standard deviation). The main reason for ED presentations was a mental health crisis. The three most frequent areas of need requiring action were mood (43.8%), suicide risk (37.4%), and parent-child relational problems (34.6%). During the ED visit, 21.6% of patients received medical clearance, 40.9% received a psychiatric consult, and 19.4% were admitted to inpatient psychiatric care. At the 1-month post-ED visit, 84.3% of patients/caregivers received mental health follow-up. Ratings of service recommendations were generally positive, as 60.9% of patients obtained the recommended follow-up care and 13.9% were wait-listed. Conclusions: Children and youth and their families presenting to the ED with mental health needs had substantial clinical morbidity, were connected with services, were satisfied with their ED visit, and accessed follow-up care within 1-month with some variability. RÉSUMÉ: Objectifs: L'étude visait à examiner les besoins, en santé mentale, de jeunes et d'enfants ayant consulté au service des urgences (SU) pour des troubles de santé mentale, et à décrire le type de suivi assuré par les services de santé mentale et le degré de satisfaction des participants. Méthode: Une étude de cohorte prospective, d'une durée de 6 mois à 18 mois, y compris 1 mois de suivi après le congé du SU, a été menée dans trois SU pédiatriques et un SU générales, au Canada. Les mesures comprenaient a) l'évaluation des besoins en santé mentale par le clinicien; b) l'appréciation des services de suivi par les patients et les aidants; et c) les entretiens sur le degré de satisfaction des participants quant au suivi. L'analyse des données comprenait des statistiques descriptives ainsi qu'un test selon la méthode exacte de Fisher pour permettre une comparaison entre les centres. Résultats: La cohorte se composait de 373 jeunes et enfants (filles : 61, 1 %; âge moyen : 15, 1 ans; écart-type : 1, 5). Le principal motif de consultation au SU était un trouble de santé mentale qui avait évolué en crise. Les trois principaux types de besoins nécessitant des interventions étaient des troubles de l'humeur (43, 8 %), le risque de suicide (37, 4 %) et des problèmes de relations entre parents et enfants (34, 6 %). Durant les consultations au SU, 21, 6 % des patients ont reçu leur congé après autorisation médicale; 40, 9 % ont obtenu une consultation en psychiatrie et 19, 4 % ont été hospitalisés au service de psychiatrie. Un mois après la consultation au SU, 84, 3 % des patients ou des aidants ont été joints pour un suivi en santé mentale. Dans l'ensemble, l'évaluation des recommandations concernant les services était bonne; 60, 9 % des patients avaient obtenu les soins de suivi recommandés et 13, 9 % des patients étaient inscrits sur une liste d'attente. Conclusions: Les jeunes et les enfants ainsi que les membres de leur famille ayant consulté au SU pour des troubles de santé mentale présentaient des signes cliniques importants de morbidité, ont été mis en lien avec des services, se sont montrés satisfaits de la consultation au SU et ont obtenu, à divers degrés, des soins de suivi au bout de 1 mois.